2004
DOI: 10.1080/15287390490492430
|View full text |Cite
|
Sign up to set email alerts
|

Urban Wet-Weather Flows: Sources of Fecal Contamination Impacting on Recreational Waters and Threatening Drinking-Water Sources

Abstract: Discharges of urban stormwater and combined sewer overflows (CSOs) contribute to fecal contamination of urban waters and need to be considered in planning the protection of recreational waters and sources of drinking water. Stormwater characterization indicates that Escherichia coli counts in stormwater typically range from 103 to 104 units per 100 ml. Higher counts (10(5) units/100 ml) suggest the presence of cross-connections with sanitary sewers, and such connections should be identified and corrected. Feca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 17 publications
5
83
1
2
Order By: Relevance
“…Since there are no combined sewers in the Tucson Basin, overflow of untreated sewage is not a potential source of E. coli (e.g. Arnone and Walling, 2007;Marsalek and Rochfort, 2004).…”
Section: Runoff Quality Responsesmentioning
confidence: 99%
“…Since there are no combined sewers in the Tucson Basin, overflow of untreated sewage is not a potential source of E. coli (e.g. Arnone and Walling, 2007;Marsalek and Rochfort, 2004).…”
Section: Runoff Quality Responsesmentioning
confidence: 99%
“…The surface water outbreaks tended to occur within a month of the storm, and monitoring confirmed that coliform bacteria levels rise dramatically during or immediately following storm events (Hyland et al, 2003;Marsalek and Rochfort, 2004). Coliform bacteria are typically not harmful to humans, but they are monitored as indicator organisms to detect the possible presence of fecal contamination and human health risks.…”
mentioning
confidence: 99%
“…CSOs may represent a health risk for people in contact with these waters since the principal source of bacteria it contains is from human waste, which can contain large quantities of fecal pathogens [22]. E. coli concentration associated with CSOs can reach more than 10 6 /100ml, which it is much higher than recreational water guidelines [23]. Wastewater treated by wastewater treatment plants can also contain large amounts of fecal bacteria if these waters are not disinfected before being discharged into watercourses, placing people swimming in waters in close proximity to these discharges at higher risk for health problems [24].…”
Section: Urban Activitiesmentioning
confidence: 99%